The Influence of ESG Disclosure and GCG on Financial Performance of Mining Companies in Indonesia - Dahlan, Achmad Ramdhoni; Tarigan, Samuel (Jurnal Locus Penelitian dan Pengabdian, 2025)
Sustainability issues are an important concern in business and investment decision-making. The mining sector has significant environmental and social impacts, the implementation of ESG and Good Corporate Governance (GCG) practices is key in realizing optimal and sustainable financial performance. This study aims to analyze the influence of Environmental, Social, and Governance (ESG) and Good Corporate Governance (GCG) disclosures on the financial performance of mining companies in Indonesia. The independent variables in this study include the ESG score from the Katadata ESG Index 2024 and GCG which are proxied through the size of the board of directors, independent board of commissioners, and institutional ownership, company size as a control variable, while the independent variable of financial performance is measured by Return on Equity (ROE). The underlying theories of this research include agency theory, stakeholder theory, and legitimacy theory which explain the importance of accountability and harmonious relationships with stakeholders in driving company performance. The results of multiple linear regression on 44 mining company samples showed that only partially the size of the board of directors variables had a positive and significant effect on ROE. Meanwhile, simultaneously, all independent variables have a significant effect on ROE. These findings confirm the importance of the board structure in supporting financial performance, while other ESG and GCG influences have not had a direct impact individually.